Mengajarkan Tahfiz al-Qur’an Menggunakan Metode Talaqqi Selama Masa KKN di SD IT Anshorul Jadid - Syahru Ridho (Academia Publication, 2021)
Anshorul Jadid Integrated Islamic Elementary School is an integrated Islamic-based school that contains Islamic religious lessons in its subjects. However, because the students are still at the elementary school level, the way to teach it also cannot be done in a random way, so here the talaqqi method is chosen in teaching it, namely by reading, dictating and practicing directly in the field when teaching, so that students can easily accept the material that is taught. taught at the same time easy also when imitating the practice being taught, so that the results of teaching in the form of increasing the ability of students to understand and master the material being taught